Bayesian semiparametric stochastic volatility modeling - Mark J. Jensen; John M. Maheu (Federal Reserve Bank of Atlanta, 2008)
This paper extends the existing fully parametric Bayesian literature on stochastic volatility to allow for more general return distributions. Instead of specifying a particular distribution for the return innovation, we use nonparametric Bayesian methods to flexibly model the skewness and kurtosis of the distribution while continuing to model the dynamics of volatility with a parametric structure. Our semiparametric Bayesian approach provides a full characterization of parametric and distributional uncertainty. We present a Markov chain Monte Carlo sampling approach to estimation with theoretical and computational issues for simulation from the posterior predictive distributions. The new model is assessed based on simulation evidence, an empirical example, and comparison to parametric models.
Keywords: C11; C14; C53; 330; Bayesian nonparametrics; Dirichlet process mixture prior; Markov chain Monte Carlo; mixture models; stochastic volatility